Clinical and microbiological profile of urinary tract infection in children less than five years of age - N, Madhu G; S, Harish; Sharanappa, Siva (Indian Journal of Child Health, 2018)
Background: Urinary tract infection (UTI) is a common bacterial illness of pediatric age group. UTIs, especially in young children, have non-specific signs and symptoms that can be undetected or misdiagnosed. Delaying diagnosis and treatment of UTIs may result in long-term renal complications. Objectives: The objectives were to study the clinical presentation of UTI, common uropathogens, and antimicrobial sensitivity pattern among children <5 years of age. Materials and Methods: This is a hospital based prospective descriptive study which included 100 children <5 years of age who presented with UTI over a period of 1 year. Detailed history, clinical examination, and laboratory investigations including urine analysis and culture were documented. Results: Out of the 100 children below 5 years who presented with UTI, 32% were below 1 year age. Male to female ratio in our study was 2.8:1. The most common presenting symptom was fever followed by crying during micturition. 92% of the cases had significant pyuria. Escherichia coli is the most common pathogen isolated (68%), followed by Klebsiella and Enterococcus. 62% had abnormal ultrasonography findings, most common being hydronephrosis (36%). Conclusions: The presentation of pediatric UTIs varies widely with age and sex. Knowledge of the varied presentation of UTI, its risk factors and local antimicrobial sensitivity patterns are of great significance in preventing future complications in children.